Antimalarial Activity of Extract and Fractions of Sauropus androgynus (L.) Merr. (8th September 2022) - Ekasari, Wiwied; Fatmawati, Dwi; Khoiriah, Siti M.; Baqiuddin, Wenda A.; Nisa, Hawi Q.; Maharupini, Adinda A. S.; Wahyuni, Tutik S.; Oktarina, Rice D.; Suhartono, Eko; Sahu, Ram K.
Abstract : Sauropus androgynus (L.) Merr., in the Indonesian local name known as "Katuk, " is a tropical shrub plant of the family Euphorbiaceae. Based on genus and chemotaxonomic approaches, as well as in vitro testing of Plasmodium falciparum, leaves of S. androgynus are presumed to have an active compound content as an antimalarial. The current study aims to investigate the antimalarial activity of 96% ethanol extract and fractions of S. androgynus leaves. The ethanolic extract was fractionated using the vacuum liquid chromatography (VLC) method with three solvents of different polarities (n-hexane, chloroform, and 96% ethanol). The fraction obtained was then evaluated for antimalarial activity against P. falciparum 3D7 strain. The ethanolic extract was evaluated for antimalarial suppressive and prophylactic activity against P. berghei -infected mice, as well as inhibitory activity against the heme detoxification process in vitro. Fractionation of ethanolic extract resulted in seven combined fractions, with the most active fraction being FV (50% inhibitory concentration (IC50 ) = 2.042 µ g/mL). The ethanolic extract showed good parasitic suppressive (therapeutic) activity with a median effective dose (ED50 ) value of 15.35 mg/kg body weight. In a prophylactic test, ethanolic extract showed parasite growth inhibitory activity of 67.74 ± 9.21% after the administration of 400 mg/kg body weight for 4 days before infection, and 65.30 ± 10.44% after the administration of 200 mg/kg body weight for 8 consecutive days (4 days before and after infection). The ethanolic extract also showed an effect in inhibiting the formation of β -hematin of about 26.87–79.36% at a concentration of 0.1–4 mg/mL and an IC50 value of 0.479 mg/mL. The S. androgynus leaves were shown to have antimalarial activity in vitro and in vivo, where ethanolic extract were more active compared with the fraction obtained. The antimalarial properties of the extract showed a higher suppressive activity than prophylactic activity.